Integrating digital technology and local wisdom in smart ecotourism: A community-based approach in Brastagi - Daryana, Aditiya Pratama; Waluyo, Bakti Dwi (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Digital transformation and the need for sustainable tourism have driven the emergence of smart ecotourism that blends technology with local cultural values. Brastagi, North Sumatra, as a leading destination based on agrotourism and Karo culture, faces the challenge of low utilization of digital technology in supporting tourist attractions. This research aims to identify the integration of digital technology and local wisdom in the development of community-based smart ecotourism in Brastagi, as well as evaluate the readiness and perception of local communities towards its implementation. The method used was a mixed exploration approach, involving a survey of 100 tourists as well as in-depth interviews and field observations of 15 tourism actors and traditional leaders. Quantitative analysis was conducted using SPSS software, while qualitative analysis used thematic coding techniques. The results show a high interest among travellers in digital experiences that blend local cultural narratives, with 76% of respondents expressing interest and 59% willing to pay more for augmented reality-based content or QR codes. However, limited infrastructure and low digital literacy are the main obstacles. This study concludes that the success of smart ecotourism development depends on the synergy of digital innovation and the local socio-cultural context, with the active involvement of the community as a key factor to create sustainable and authentic destinations.